Price Behavior of Beef and Chicken Meat in Indonesia - Raslea Azalia; Ketut Sukiyono; Nola Windirah (Faculty of Animal Science, Universitas Brawijaya, 2023)
Stabilization of food prices is still a strategic issue in Indonesia. This is because most Indonesians use their income mostly for food. Various publications reported that Indonesian food expenditure is approximately half of their income. Therefore, maintaining price stability, including beef and chicken meat price, is a significant policy to design. However, the continuous difficulty in predicting how beef and chicken meat prices behave is another reason for the importance of analyzing the price behavior of these two commodities. This research aims to respond to these problems by analyzing price fluctuations and price trends in beef and chicken meat commodities in Indonesia. The data used is monthly beef and chicken meat prices in Indonesia from January 2018 until December 2022, or 60 observations. Analysis of price fluctuations (instability) and trend analysis is applied. The results show that commodity chicken meat has a higher instability (fluctuation) than beef price. Both beef and chicken meat trend show a quadratic pattern, with an increasing trend for beef and a decreasing trend for chicken meat.